2019
DOI: 10.1007/s00262-019-02446-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutation burden and immunological, genomic, and clinicopathological factors as biomarkers for checkpoint inhibitor treatment of patients with non-small-cell lung cancer

Abstract: Tumor mutation burden and immunological, genomic, and clinicopathological factors as biomarkers for checkpoint inhibitor treatment of patients with non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Previous studies have indicated that NTRK3 affects multiple signaling pathways, including the MAPK and PI3K pathways, which further promote cell differentiation and affect tumor progression (Jin et al, 2010;Ozaki et al, 2020). Similarly, some effects on these pathways correlate with NTRK3 mutations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have indicated that NTRK3 affects multiple signaling pathways, including the MAPK and PI3K pathways, which further promote cell differentiation and affect tumor progression (Jin et al, 2010;Ozaki et al, 2020). Similarly, some effects on these pathways correlate with NTRK3 mutations.…”
Section: Discussionmentioning
confidence: 97%
“…Although ICIs are widely used in cancer treatment, predictive biomarkers for prognosis of patients to ICIs are not well established. Regardless, PD-L1 expression, TMB, NAL and microsatellite instability (MSI) status are promising biomarkers for ICIs, even though their predictive ability remains limited (Ozaki et al, 2020). Therefore, biomarkers that are more accurate and clinically useful than these biomarkers for predicting the efficacy of ICI treatment are needed.…”
Section: Discussionmentioning
confidence: 99%
“…For those without recurrence or death by the end of follow-up, survival end points were censored at the date of last follow-up. 23 A Cox proportionalhazard model was constructed for OS in multivariate analysis. Backward selection was used to adjust potential confounding covariate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 59 ] Another study also reports that TMB is associated with the EGFR -wild lung cancers. [ 60 ] Interestingly, a study reports that durvalumab improves the objective response (OR) of EGFR / ALK -mutated NSCLC patients with ≥25% of PD-L1 expression. [ 61 ] Furthermore, a combination of atezolizumab with tyrosine kinase inhibitor (TKI) is shown to be effective on TKI-invalid patients with EGFR mutation.…”
Section: Biomarkersmentioning
confidence: 99%